STABILITY ENHANCEMENT OF NANO-NiO CATALYST WITH SiO2 SUPPORT TO GET IMPROVED HYDROGEN YIELD FROM METHANE DECOMPOSITION - Ashik, U; Daud, W W (MATTER: International Journal of Science and Technology, 2016)
The building of the nanoparticle from their precursors by the bottom-up method is a very fascinating practice in nanotechnology. Most promising two bottom-up methods are experimentally unveiled in this research contribution; i) controlled precipitation of Ni nanoparticles and their reinforcement with silicate by the modified Stöber method and ii) chemical vapor deposition of nano-carbon from methane over silicate supported nano-Ni catalyst. We found that the silicate addition results in the formation of single crystal NiO nanoparticles which exhibited catalytic activity-enhancing features, such as low particle size and high surface area and porosity. The single-point surface area was increased from 62.22 m2/g to 91.50 m2/g for n-Ni O nanoparticles, after silicate incorporation. Preliminary catalytic activity was also analyzed in a fixed-bed pilot plant. N-NiO/SiO2 nanoparticles generated 57.28% hydrogen at 730 °C. Isothermal methane decomposition was conducted at 625 °C to examine the stability of the catalyst.